2015
DOI: 10.7326/m15-0452
|View full text |Cite
|
Sign up to set email alerts
|

Combined Diet and Physical Activity Promotion Programs to Prevent Type 2 Diabetes Among Persons at Increased Risk: A Systematic Review for the Community Preventive Services Task Force

Abstract: Background Trials have demonstrated the efficacy of rigorous diet and physical activity promotion (D&PA) programs for adults at increased risk for type 2 diabetes to reduce diabetes incidence and improve measures of glycemia. Purpose To evaluate D&PA programs for individuals at increased risk for type 2 diabetes primarily to lower diabetes risk, lower body weight, and improve glycemia. Data Sources MEDLINE, Cochrane Central Register of Controlled Trials, CAB Abstracts, Global Health, and Ovid HealthStar fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
229
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 296 publications
(238 citation statements)
references
References 118 publications
7
229
0
2
Order By: Relevance
“…23,24 Importantly, potential interventions like diet and physical activity promotion programs in prediabetes have been shown to reduces glucose levels. 38 Furthermore, physical exercise have been shown to reduce the odds ratio of hyperfiltration and to modify the effect of fasting glucose on GFR. 39 In addition, new treatment options in hyperglycemia like the Sodium/Glucose Cotransporter 2 (SGLT2) inhibitors may prevent hyperfiltration independently of the glucose lowering effect.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Importantly, potential interventions like diet and physical activity promotion programs in prediabetes have been shown to reduces glucose levels. 38 Furthermore, physical exercise have been shown to reduce the odds ratio of hyperfiltration and to modify the effect of fasting glucose on GFR. 39 In addition, new treatment options in hyperglycemia like the Sodium/Glucose Cotransporter 2 (SGLT2) inhibitors may prevent hyperfiltration independently of the glucose lowering effect.…”
Section: Discussionmentioning
confidence: 99%
“…Actual cost data from the DPP and DPPOS also confirm this (12). Group delivery of DPP content into community settings has the potential to reduce overall program costs while still producing weight loss and diabetes risk reduction (13,14). The Centers for Disease Control and Prevention (CDC) helps to coordinate the National Diabetes Prevention Program, a resource designed to bring evidence-based lifestyle change programs for preventing type 2 diabetes to communities (http://www.cdc.gov/diabetes/ prevention/index.htm).…”
Section: Lifestyle Modificationmentioning
confidence: 99%
“…Therefore, life-style intervention programs should be intensive and have frequent follow-up to achieve significant weight reductions and improve clinical parameters such as lipid profile [24].Many studies found strong and consistent evidence that modest persistent weight loss can delay the progression from pre diabetes to type 2 diabetes [25,26] and is beneficial to the management of type 2 diabetes. Modest weight loss (reduction of 5% of initial body weight), has been shown to improve glycemic control and to reduce the need for glucose-lowering medications [27,28].…”
Section: Discussionmentioning
confidence: 99%